1987
DOI: 10.1038/ki.1987.265
|View full text |Cite
|
Sign up to set email alerts
|

Acute adaptative changes to unilateral nephrectomy in humans

Abstract: Renal function was monitored in 20, living-related kidney donors before and after uninephrectomy. Urinary protein excretion and retinoid metabolism respectively were studied in 10 and 6 of these donors. The functional adaptation was characterized by an increase in glomerular filtration rate and tubular function, which began in the first two days after uninephrectomy. Changes in tubular function were also demonstrated by significant increases in the urinary excretion of beta 2 microglobulin (beta 2M), retinol b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
4
26
0
2
Order By: Relevance
“…In addition, it could be demonstrated that the increase of all three parameters was paralleled by a decrease of the donor's eGFR and correlation analysis revealed a significant inverse association of eGFR with ROH, RBP4 and apoRBP4, respectively. These results confirmed and expanded the observations of Argiles et al [26], who reported an increase of ROH and RBP4 serum concentration in donors seven days after LDKT.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it could be demonstrated that the increase of all three parameters was paralleled by a decrease of the donor's eGFR and correlation analysis revealed a significant inverse association of eGFR with ROH, RBP4 and apoRBP4, respectively. These results confirmed and expanded the observations of Argiles et al [26], who reported an increase of ROH and RBP4 serum concentration in donors seven days after LDKT.…”
Section: Discussionsupporting
confidence: 92%
“…Although ATRA has been reported to inhibit the compensatory hypertrophy of the kidney after unilateral removal [20], there was no substantial difference in size among the two groups of ATRA-treated mice, the oil-treated controls, and the untreated controls. The splenic weight was also measured to determine whether ATRA could eliminate splenomegaly in IL-6 transgenic mice.…”
Section: Resultsmentioning
confidence: 81%
“…42,43 A 53% reduction in the glomerular filtration rate has been observed immediately after unilateral nephrectomy. 44 The remaining kidney is, therefore, challenged to face prolonged hyperfiltration. 45 Hemodynamics and structural changes contribute to increased renal blood flow and decreased renal vascular resistance.…”
Section: Discussionmentioning
confidence: 99%